Study of chronic hemolytic anaemia patients in Rio de Janeiro: prevalence of anti-human parvovirus B19 IgG antibodies and the developement aplastic crises - SANT'ANNA Anadayr L.M.; GARCIA Rita de Cássia N. Cubel; MARZOCHE Mônica; ROCHA Heloisa Helena A. Gallo da; PAULA Maria Tereza M.; LOBO Clarisse C.; NASCIMENTO Jussara P. (Universidade de São Paulo (USP), 2002)
The prevalence of anti-human parvovirus B19 IgG antibodies was determined in sera from 165 chronic hemolytic anemia patients, receiving medical care at Instituto Estadual de Hematologia (IEHE), Rio de Janeiro, during the year of 1994. This sample represents around 10% of the chronic hemolytic anemia patients attending at IEHE. Most of these patients (140) have sickle cell disease. Anti-B19 IgG antibodies were detected in 32.1% of patients. No statistically significant difference (p > 0.05) was seen between IgG antibody prevalence in male (27.8%) and female (35.5%) patients. Anti-B19 IgG antibodies were more frequent in older (37.6%) than younger (28.2%) than 20 years old patients, although this difference had no statistical significance (p > 0.05). Anti-B19 IgG antibody prevalence showed that 67.9% of patients enrolled in the study were susceptible to B19 acute infection. With the aim to detect acute B19 infection, patients follow up continued until February 1996. During this period four patients presented transient aplastic crisis due to human parvovirus B19 as confirmed by the detection of specific IgM antibodies. All four patients were younger than 20 years old, and 3 were younger than 10 years old. Three of them were sickle cell disease patients. Three of the four acute B19 infection occurred during 1994 springtime.